2014
DOI: 10.1007/s12671-014-0280-8
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study: Efficacy of Mindfulness-Based Cognitive Therapy versus Sertraline as First-line Treatments for Major Depressive Disorder

Abstract: Major depressive disorder (MDD) is the leading cause of disability in the developed world, yet broadly effective treatments remain elusive. The primary aim of this pilot study was to investigate the efficacy of Mindfulness-Based Cognitive Therapy (MBCT) monotherapy, compared to sertraline monotherapy, for patients with acute MDD. This open-label, nonrandomized controlled trial examined a MBCT cohort (N=23) recruited to match the gender, age, and depression severity of a depressed control group (N=20) that comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
2
16
1
Order By: Relevance
“…However, it should be noted that the effect sizes observed are similar to those reported in a study that documented pre-to post-intervention changes in depressive symptoms in patients randomised to MBCT or treatment as usual (van Aalderen et al 2012). Where substantially larger effects have been observed, these have been based on small samples (Barnhofer et al 2009;Chiesa et al 2015;Eisendrath et al 2015;Kingston et al 2007). In the present study, the effect on PHQ-9 symptoms was smaller compared to interventions offered in IAPT services overall for depression cases (1.4; Clark 2018).…”
Section: Discussioncontrasting
confidence: 54%
“…However, it should be noted that the effect sizes observed are similar to those reported in a study that documented pre-to post-intervention changes in depressive symptoms in patients randomised to MBCT or treatment as usual (van Aalderen et al 2012). Where substantially larger effects have been observed, these have been based on small samples (Barnhofer et al 2009;Chiesa et al 2015;Eisendrath et al 2015;Kingston et al 2007). In the present study, the effect on PHQ-9 symptoms was smaller compared to interventions offered in IAPT services overall for depression cases (1.4; Clark 2018).…”
Section: Discussioncontrasting
confidence: 54%
“…Finally, Eisendrath et al . [21**] present initial data to suggest that MBCT may be an effective first-line treatment in acute depression relative to Sertraline, suggesting MBCT’s value for patients who cannot tolerate side effects or do not respond to an initial trial of antidepressant medication.…”
Section: Extensions Of the Mbct Modelmentioning
confidence: 99%
“…Mindfulness-based interventions, such as mindfulness-based stress reduction (MBSR) and mindfulness-based cognitive therapy (MBCT), involve training in attention and emotional regulation ( 10 , 11 ) and are delivered in group format. There is accumulating evidence that MBCT and MBSR may be helpful for depression, and anxiety: MBCT has demonstrated effectiveness for relapse prevention in patients with severe, chronic major depressive disorder ( 12 ), and MBSR and MBCT appear useful for depression ( 13 , 14 ) and generalized anxiety disorder (GAD) ( 15 ). Recent studies have suggested that mindfulness training may also be a useful component for treatment of PTSD.…”
Section: Introductionmentioning
confidence: 99%